2022
DOI: 10.1126/scisignal.abl9169
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR screen targeting PI3K effectors identifies RASA3 as a negative regulator of LFA-1–mediated adhesion in T cells

Abstract: The integrin lymphocyte function–associated antigen 1 (LFA-1) helps to coordinate the migration, adhesion, and activation of T cells through interactions with intercellular adhesion molecule 1 (ICAM-1) and ICAM-2. LFA-1 is activated during the engagement of chemokine receptors and the T cell receptor (TCR) through inside-out signaling, a process that is partially mediated by phosphoinositide 3-kinase (PI3K) and its product phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ). To evaluate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
(146 reference statements)
2
7
0
Order By: Relevance
“…We examined the impact of the loss of Rasa3 and Sipa1 in T cells in vivo . Compared to WT mice, Rasa3 -KO mice exhibited decreases in both the percentages and numbers of CD3 + T cells in superficial LNs (SLNs) and blood, while T-cell numbers were normal in Sipa1 -KO mice ( Figures S1A, B ), as previously reported ( 26 , 33 ). The absence of Rasa3 and Sipa1 decreased the numbers of CD3 + T cells in SLNs and to a greater extent in the spleen and blood ( Figures 2A, B ; S1A, B ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…We examined the impact of the loss of Rasa3 and Sipa1 in T cells in vivo . Compared to WT mice, Rasa3 -KO mice exhibited decreases in both the percentages and numbers of CD3 + T cells in superficial LNs (SLNs) and blood, while T-cell numbers were normal in Sipa1 -KO mice ( Figures S1A, B ), as previously reported ( 26 , 33 ). The absence of Rasa3 and Sipa1 decreased the numbers of CD3 + T cells in SLNs and to a greater extent in the spleen and blood ( Figures 2A, B ; S1A, B ).…”
Section: Resultssupporting
confidence: 85%
“…T-cell–specific deletion of Rasa3 did not appear to affect T-cell homeostasis in the thymus or periphery but did impair Th17 production in experimental autoimmune encephalomyelitis model mice ( 32 ). A recent study reported that the lack of Rasa3 in T cells increased T-cell receptor (TCR)–triggered binding to soluble ICAM1 and impaired T-cell entry into and egress from peripheral LNs ( 33 ). However, the precise mechanisms by which Rap-GAPs regulate T-cell trafficking have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar capillary endothelial cells not only functioned as gas exchangers, but were also capable of recruiting immune cells through adhesion molecules and activating CD4 + T cells [ 31 ]. By binding to T cell integrin, ICAM1 increased T cell receptor (TCR) signaling to mediate the activation, adhesion, and migration of T cells [ 32 , 33 ]. Patients with COVID-19 showed pulmonary vascular injury associated with intracellular presence of SARS-CoV-2 and endothelial cell destruction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schwartzberg et al. conducted a CRISPR knockout screen in CD8 + T cells using a PIP3-binding protein CRISPR library to identify genes influencing the binding ability of primary mouse T cells to ICAM1 ( 122 ). RASA3 was identified as the potential target gene by comparing sgRNA frequencies between scICAM1 neg (not binding ICAM1) and scICAM1 pos (ICAM1-binding) cells.…”
Section: Crispr Screening In Immune Cellsmentioning
confidence: 99%